Optimizing Kinect: Audio and Acoustics (keynote) - Tashev, Ivan (Inormation Technologies and Applications Workshop, 2012)
The engineering is almost always trade-offs between controversial requirements. Important role in finding the best design solutions under such requirements play the methods of mathematical optimization. Properly defined optimization criterion and constraints convert these mathematical methods to solvers of real engineering problems. The talk will cover the approaches for optimizing the acoustical design and the algorithms in the audio pipeline of Kinect – the bestselling electronic device in the history of mankind as recorded in the Guinness Book or Records. This is the first industrial product with surround sound echo cancellation, hands-free sound capture and speech recognition for distances up to 3.5 meters, and the first open microphone device which doesn’t need push-to-talk button to start the speech recognition. It wouldn’t be successful without pushing the acoustical design and the algorithms to their limits using optimization methods.